2014
DOI: 10.5812/iranjradiol.7054
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Mediastinal Thyroid Tissue with a Normally Located Thyroid Gland

Abstract: Ectopic thyroid tissue (ETT) is a rare entity and a challenging differential diagnosis. This is a report of a case of a mediastinal mass that was found to be an ectopic mediastinal thyroid tissue, in a 77-year-old woman who was admitted to our hospital for breast cancer management. The mediastinal mass was identified in the postsurgical computed tomography (CT) scan of the chest and was suspected as mediastinal lymph node metastasis. A CT-guided percutaneous transthoracic punch biopsy (CT-TPB) proved to be an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In the literature investigation, we found that the CT features of the masses in the present cases were very similar to those of mediastinal ectopic thyroid reported in previous studies. [ 4 , 5 ] US and CT performed in the previous and present reports showed the mediastinal lesions as discrete masses with a mild mass effect. In addition, these lesions showed inhomogeneous enhancement on contrast-enhanced CT images.…”
Section: Discussionsupporting
confidence: 62%
“…In the literature investigation, we found that the CT features of the masses in the present cases were very similar to those of mediastinal ectopic thyroid reported in previous studies. [ 4 , 5 ] US and CT performed in the previous and present reports showed the mediastinal lesions as discrete masses with a mild mass effect. In addition, these lesions showed inhomogeneous enhancement on contrast-enhanced CT images.…”
Section: Discussionsupporting
confidence: 62%
“…As for the presence of orthotopic thyroid glands, no eutopic thyroids were observed in 70%-75% of lingual thyroids, and in addition, most of the lingual thyroid cases were hypothyroidism [5,11,12]. In reports of mediastinal ectopic thyroids, they seemed to have orthotopic thyroid and euthyroid function in most of the cases [5,7,8,[13][14][15][16][17][18]. However, Santangelo et al reported five cases of ectopic thyroids in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid completes its descent in the seventh gestational week. Presence of ectopic thyroid tissues in distant locations could happen as a result of abnormal migration or heterotopic differentiation of uncommitted endodermal cells 4…”
Section: Discussionmentioning
confidence: 99%